Kekerasan Verbal dalam Dakwah (Studi Kasus Rekaman Ceramah Aman Abdurrahman) - Mustofa Hilmi; Zumrotul Choiriyah (Al-Mada: Jurnal Agama, Sosial, dan Budaya, 2022)
This research aims to determine the verbal abuses in speech. The main focus of this research is to know what are the forms of verbal abuse in Aman Abdurrahaman's "tauhid" speech. In this research, the categories of verbal abuse are associated with animals, swearing, stigmatization or labeling, euphemism, and dysphemism. The type of this research is qualitative research. The researcher uses a descriptive content analysis approach. In this research, the data was obtained by documentation method which is done by collecting audio and video recordings of Aman Abdurrahman’s speech about Tauhid on www.millahibrahim.net. The result shows that Aman Abdurrahman's Tauhid speech represents some verbal abuses that are associated with bad events, labeling, euphemism, and dysphemism. The verbal abuse was concocted to preach the teachings of tauhid to the people. By doing verbal abuses to the group that is excluded from his belief in tauhid, he, directly and indirectly, invites his listeners to judge the people who are outside of his group as deviants or in other terms, to stipulate his group as the most righteous one. The forms of verbal abuses performed by Aman Abdurrahman show that he was giving clear boundaries between Muslims and kafir; believers and nonbelievers; true and false; Tauhid and shirk. These attempts were made to spread the purity of monotheism teaching, which he considers as the Islamic, assertive, and firm lecture.